Modeling And Analysis Of Lateral Doping Region Translation Variation On Optical Modulator Performance - Sahbudin, Saari; Hanim, Abdul Razak; Mardiana, Bidin; Haroon, Hazura; Menon, P.S (2010)
In this paper, we design and discuss the performance of a silicon phase modulator integrated in a silicon‐on‐insulator (SOI) waveguide. The modulator employing the p‐i‐n diode structure will be working at 1.55 μm optical telecommunications wavelengths. The lateral translation of doping regions of p+ and n+ doping regions are varied, and the refractive index change, phase modulation efficiency and also the absorption loss of the modulator are investigated. Our simulation shows that moving the lateral translation of the doping regions closer to the rib waveguide sidewall, the change of the refractive index increases, resulting better modulation efficiency but experiences more absorption loss.